Exploring uses of maritime surveillance data for marine spatial planning: A review of scientific literature. (July 2020) - Dupont, Clément; Gourmelon, Françoise; Meur-Ferec, Catherine; Herpers, Frédérick; Le Visage, Christophe
Abstract: Maritime Spatial Planning (MSP) has become of key interest in many countries around the world in the last decade, leading to an increased need to inform the historical spatial and temporal footprint of maritime activities. If this knowledge was still recently considered a blind spot, recent developments of maritime surveillance systems (e.g. AIS, VTS, VMS) have allowed to fill some of these gaps by generating significant amounts of spatial data on ships at sea. In this paper, the use of these maritime surveillance data for planning purposes is explored through the lens of the international scientific literature. A first set of 2030 articles dealing with maritime surveillance data and collected through the Web of Science collection was explored to determine the type of data used, the maritime activities addressed and the main objective of each paper (technical developments, safety and security, environmental protection, MSP). This allowed to highlight the growing interest on maritime surveillance data in the scientific literature over the past decades, predominantly towards AIS data and shipping. Over the 2030 papers, only 63 dealt specifically with MSP. These were extracted and explored, allowing to highlight the potential of these data to feed in MSP processes, with a specific focus on fisheries. Nevertheless, the description of actual uses of surveillance-based information within MSP processes remained particularly rare. If this can be seen as a result of a science-policy delay, we suggest that it is mostly related to issues of accessibility, acceptance by economic stakeholders and appropriation by decision makers. Highlights: Maritime surveillance data have been widely addressed in the scientific literature. Most researches aim at improving the instantaneous maritime situational awareness. There is an emerging interest on the potential uses of these data in delayed time. This can fill the knowledge gap on maritime activities' spatiotemporal footprint. This knowledge can be a significant input to marine spatial planning.